2020
DOI: 10.1016/j.jcat.2020.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic micro–mesoporous composites with center-radial pores assembled by TS-1 nanocrystals to enhance hydrodesulfurization activity of dibenzothiophene and 4,6-dimethyldibenzothiophene

Abstract: A novel dendritic composite (TD) with an open center-radial pore structure using TS-1 nanocrystals as microporous precursors were synthesized successfully by a facile method. TS-1 nanocrystals were embedded into the framework of dendritic mesoporous silica nanospheres (DMSNs) to form Si-O-Ti bonds, which was beneficial to generate more S vacancies of MoS2 active phases. NiMo/TD-2 catalyst had a larger surface area and higher metal-support-interaction (MSI), resulting in a higher sulfidation and dispersion degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…[60][61][62][63] Specifically, titano-silicate (TS-1) seeds were embedded in dendritic mesoporous silica nanoparticles (NPs) to form a composite that was later modified by NiMo via impregnation for HDS activity of DBT and 4,6-DMDBT. [60,63] In these studies, dendrimers with different structural characteristics were synthesized by virtue of varying molar composition of SiO 2 /TiO 2 (150) and CTAB/NaSal (2), to achieve highly active catalysts with highest TOF. The improved catalytic performance is associated with the increased Brønsted and Lewis acid sites, which resulted in generation of more CUS due to spillover of d-electrons from Ti-O-Si network.…”
Section: Zeolites-silicas Supportsmentioning
confidence: 99%
See 1 more Smart Citation
“…[60][61][62][63] Specifically, titano-silicate (TS-1) seeds were embedded in dendritic mesoporous silica nanoparticles (NPs) to form a composite that was later modified by NiMo via impregnation for HDS activity of DBT and 4,6-DMDBT. [60,63] In these studies, dendrimers with different structural characteristics were synthesized by virtue of varying molar composition of SiO 2 /TiO 2 (150) and CTAB/NaSal (2), to achieve highly active catalysts with highest TOF. The improved catalytic performance is associated with the increased Brønsted and Lewis acid sites, which resulted in generation of more CUS due to spillover of d-electrons from Ti-O-Si network.…”
Section: Zeolites-silicas Supportsmentioning
confidence: 99%
“…More recently, dendrimers made up of zeolite and mesoporous silica are gaining fast research interests [60–63] . Specifically, titano‐silicate (TS‐1) seeds were embedded in dendritic mesoporous silica nanoparticles (NPs) to form a composite that was later modified by NiMo via impregnation for HDS activity of DBT and 4,6‐DMDBT [60,63] . In these studies, dendrimers with different structural characteristics were synthesized by virtue of varying molar composition of SiO 2 /TiO 2 (150) and CTAB/NaSal (2), to achieve highly active catalysts with highest TOF.…”
Section: Hierarchical Hybrid‐based Supportsmentioning
confidence: 99%
“…Moreover, Ce atoms in the CeO 2 crystal can be replaced by Zr atoms to form Ce x Zr 1-x O 2 solid solutions, promoting the generation of more oxygen vacancies and thermal stability of CeO 2 [33,34]. Our previous work [35,36] demonstrated that dendritic catalysts with open-pore channels could easily enable the reactants and products to enter into and out of their pores with lower diffusion resistance to access the active phases. However, the Ce x Zr…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that unsubstituted 4,6-DMDBT HDS reaction is more dependent on the DDS path, where it not only reacts faster but also results in desulfurization under the premise of ensuring that the aromatic rings do not increase. However, it is limited by its steric hindrance of the substituents ( Yin et al, 2013 ; Wang et al, 2020 ). In order to design and prepare a highly active hydrodesulfurization catalyst, Okamoto and Kubota (2003 ) synthesized SiO 2 -, TiO 2 -, ZrO 2 -, and Al 2 O 3 -supported catalysts using the CVD technique and found that the activity of hydrodesulfurization is positively correlated with the amount of CoMoS phases.…”
Section: Introductionmentioning
confidence: 99%